2017
DOI: 10.3389/fpsyg.2017.01330
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Connectedness to Nature Scale Based on Item Response Theory

Abstract: The Connectedness to Nature Scale (CNS) is used as a measure of the subjective cognitive connection between individuals and nature. However, to date, it has not been analyzed at the item level to confirm its quality. In the present study, we conduct such an analysis based on Item Response Theory. We employed data from previous studies using the Spanish-language version of the CNS, analyzing a sample of 1008 participants. The results show that seven items presented appropriate indices of discrimination and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 27 publications
8
45
0
2
Order By: Relevance
“…The CFA showed that, without these items, the scale gave good marks of reliability as well as a good fit of its overall factor structure. In the same way as other psychometric studies, which have suggested the advantage of deleting some items in specific cultural contexts (Olivos et al, 2011; Pasca et al, 2017), this result demonstrates the interest of proposing a new version of this scale, in order to obtain the best psychometric qualities in the French version.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The CFA showed that, without these items, the scale gave good marks of reliability as well as a good fit of its overall factor structure. In the same way as other psychometric studies, which have suggested the advantage of deleting some items in specific cultural contexts (Olivos et al, 2011; Pasca et al, 2017), this result demonstrates the interest of proposing a new version of this scale, in order to obtain the best psychometric qualities in the French version.…”
Section: Discussionsupporting
confidence: 78%
“…To measure it, the authors presented the “Connectedness to Nature Scale” (CNS), probably the most studied scale (e.g., Frantz et al, 2005; Dutcher et al, 2007; Mayer et al, 2009; Nisbet et al, 2009; Perrin and Benassi, 2009; Brugger et al, 2011; Pasca et al, 2017). The authors’ analysis of the scale achieved an alpha score of 0.84 (Mayer and Frantz, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These results add evidence for convergent validity of the RV construct because preservation, appreciation, and RVs reflect a positive attitude toward nature. Comparable studies for other measurement tools reported similar correlations to verify convergent validity (Mayer and Frantz, 2004;Perkins, 2010;Pasca et al, 2017).…”
Section: Convergent and Discriminant Validitymentioning
confidence: 71%
“…Since Mayer and Frantz (2004) carried out five surveys in their study, the factor loadings were averaged based on the number of participants. Validity, reliability, and correct measurement of connectedness to nature were proven for a reduced CNS (Pasca et al, 2017).…”
Section: Connectedness To Nature Scalementioning
confidence: 99%
“…This helped to refine the instruments by excluding items that failed to represent constructs as well as threatened internal consistency of the instrument. Similarly, Pasca, Aragonés, and Coello (2017) refined the connectedness to nature scale (Mayer & Frantz, 2004) by checking the scale's dimensionality within the framework of item response theory and found that several items failed to represent the construct of connectedness with nature.…”
Section: Recommendationsmentioning
confidence: 99%